Front Cover: Bimetallic Platinum‐Tin Nanoparticles on Hydrogenated Molybdenum Oxide for the Selective Hydrogenation of Functionalized Nitroarenes (ChemCatChem 22/2017). Issue 22 (27th November 2017) - Shu, Yijin; Chan, Hang Cheong; Xie, Lifang; Shi, Zhangping; Tang, Yi; Gao, Qingsheng
Abstract : The Front Cover shows the efficient and selective hydrogenation of functionalized nitroarenes to corresponding anilines on bimetallic Pt‐Sn supported by hydrogenated MoO x . In their Full Paper, Y. J. Shu et al. demonstrate that Pt‐Sn/H‐MoO x catalysts deliver high selectivity and activity for the hydrogenation of functionalized nitroarenes under mild conditions, as a result of the atom‐rearranged bimetallic Pt‐Sn surface and the electronic metal–support interactions with H‐MoO x, respectively. More information can be found in the Full Paper by Y. J. Shu et al. onpage 4199 in Issue 22, 2017 (DOI:10.1002/cctc.201700880 ).